Green tea intake is associated with urinary estrogen profiles in Japanese-American women - Fuhrman, Barbara J (BioMed Central, 2013)
SCOPE: Intake of green tea may reduce the risk of breast cancer; polyphenols in this drink can influence enzymes that metabolize estrogens, known causal factors in breast cancer etiology. METHODS AND RESULTS: We examined the associations of green tea intake (<1 time/week, 1-6 times weekly, or 7+ times weekly) with urinary estrogens and estrogen metabolites (jointly EM) in a cross-sectional sample of healthy Japanese American women, including 119 premenopausal women in luteal phase and 72 postmenopausal women. We fit robust regression models to each log-transformed EM concentration (picomoles per mg creatinine), adjusting for age and study center. In premenopausal women, intake of green tea was associated with lower luteal total EM (P trend = 0.01) and lower urinary 16-pathway EM (P trend = 0.01). In postmenopausal women, urinary estrone and estradiol were approximately 20% and 40% lower (P trend = 0.01 and 0.05, respectively) in women drinking green tea daily compared to those drinking <1 time/week. Adjustment for potential confounders (age at menarche, parity/age at first birth, body mass index, Asian birthplace, soy) did not change these associations. CONCLUSIONS: Findings suggest that intake of green tea may modify estrogen metabolism or conjugation and in this way may influence breast cancer risk.